Modelling of net flows to investment funds - Simanauskas, Leonas; Rutkauskas, Aleksandras Vytautas; Kucko, Irena (Journal of Business Economics and Management, 2003)
The paper presents the general model of net flows to investment funds, which helps to analyse the flows and to solve the problem structurally. The model includes various investment guidelines and different fund types, aspects of risk influence are discussed separately. Furthermore, the conception and techniques of integrated assets and liabilities portfolio management are applied forming and managing the portfolio of investment fund. Integrated assets and liabilities management is based on computerised decision models that represent both the assets and liabilities associated with the business line, characterise the uncertainty of the future environment and produce strategies for structuring the assets and liabilities in business ways that are profitable across a range of alternative future environments. The methods of imitative modelling are used and obtained results are presented in geometrical form of portfolio sets, their efficiency zones, density and survival functions. First Published Online: 14 Oct 2010